Experentia Et Progressus: An Experiential Needs Assessment of Military Health care Providers in Treating Pediatric Combat Trauma - Tovar, Matthew A; Lara, Sebastian W; Rudinsky, Sherri L; Bibbens, Sara E (Military medicine, 2025)
Children are among the most vulnerable populations affected by armed conflicts, yet there is limited data on the preparedness of military medical personnel to care for pediatric combat trauma casualties in austere or large-scale combat operations. This study aimed to assess the confidence, training needs, and resource requirements of military medical providers who have managed pediatric patients during deployment. This IRB-exempt, cross-sectional mixed-methods study used a survey created via a modified Delphi method with input from subject matter experts. The survey was distributed to active duty and reservist physicians, nurses, medics, and corpsmen who had previously deployed to combat environments. Respondents answered Likert-style questions anonymously on the SurveyMonkey platform. Data were analyzed using Welch's t-test, with statistical significance defined as P < .05. Qualitative data were coded into discrete themes and summarized. A total of 84 respondents participated in the survey. Only 27% reported feeling confident or very confident in resuscitating pediatric casualties. Health care providers with prior exposure to pediatric patients reported significantly higher confidence in pediatric trauma resuscitation (P = .02). Key factors contributing to low confidence included difficulty with pediatric medication dosing, anatomical and physiological differences, lack of experience, and insufficient pediatric-specific equipment during deployment. Nearly all respondents with prior pediatric combat trauma experience expressed a desire for additional pediatric-specific predeployment training, with nearly half (47%) advocating for more robust military-civilian trauma center partnerships. Furthermore, 59% of respondents felt they lacked adequate emotional support following negative pediatric events and recommended stronger post-traumatic event debriefing and support mechanisms. Many recently deployed military medical providers reported low confidence in resuscitating pediatric patients in the combat environment, because of drug dosing, anatomic and physiologic differences, and inexperience. Regardless of specialty, almost all providers requested additional pediatric training to improve baseline preparedness. These results can guide future predeployment training and inform policy to reduce unnecessary pediatric mortality on the battlefield.